Uniqueness in some higher order elliptic boundary value problems in n dimensional domains - Cristian-Paul Danet (Electronic Journal of Qualitative Theory of Differential Equations, 2011)
We develop maximum principles for several P functions which are defined on solutions to equations of fourth and sixth order (including a equation which arises in plate theory and bending of cylindrical shells). As a consequence, we obtain uniqueness results for fourth and sixth order boundary value problems in arbitrary n dimensional domains.